Performance of Clinical Signs in the Diagnosis of Dehydration in Children with Acute Gastroenteritis - Hoxha, Teuta (Med Arch, 2015)
BACKGROUND: Acute evaluation and treatment of children presenting with dehydration represent one of the most common situation in the pediatric emergency department. To identify dehydration in infants and children before treatment, a number of symptoms and clinical signs have been evaluated. The aim of the study was to describe the performance of clinical signs in detecting dehydration in children. METHODS: Two hundred children aged 1 month to 5 year were involved in our prospective study. The clinical assessment consisted of the ten clinical signs of dehydration, including those recommended by WHO (World Health Organization), heart rate, and capillary refill time. RESULTS: Two hundred patients with diarrhea were enrolled in the study. The mean age was 15.62±9.03 months and 57.5% were male. Of these 121 had a fluid deficit of < 5%, 68 had a deficit of 5 to 9% and 11(5.5%) had a deficit of 10% or more. Patients classified as having no or mild, moderate, and severe dehydration were found to have the following respective gains in percent weight at the end of illness: 2.44±0.3, 6.05± 1.01 and, 10.66± 0.28, respectively. All clinical signs were found more frequently with increasing amounts of dehydration(p<0.001, One–way ANOVA). The median number of findings among subjects with no or mild dehydration (deficit <5%) was 3; among those with moderate dehydration (deficit 5% to 9%) was 6.5 and among those with severe dehydration (deficit >10%) the median was 9 (p<0.0001, Kruskal-Wallis test). Using stepwise linear regression and a p value of <0.05 for entry into the model, a four-variable model including sunken eyes, skin elasticity, week radial pulse, and general appearance was derived. CONCLUSION: None of the 10 findings studied, is sufficiently accurate to be used in isolation. When considered together, sunken eyes, decreased skin turgor, weak pulse and general appearance provide the best explanatory power of the physical signs considered.